2021
DOI: 10.2147/ijn.s313093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Biochemical and Molecular Evaluations of Ivermectin Mucoadhesive Nanosuspension Nasal Spray in Reducing Upper Respiratory Symptoms of Mild COVID-19

Abstract: Background Ivermectin is an FDA-approved broad-spectrum anti-parasitic agent that has been shown to inhibit SARS-CoV-2 replication in vitro . Objective We aimed to assess the therapeutic efficacy of ivermectin mucoadhesive nanosuspension intranasal spray in treatment of patients with mild COVID-19. Methods This clinical trial included 114 patients diagnosed as mild COVID-19. Patients were divided randomly into two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“… Low (small sample size) In all the study population, the incidence of clinical deterioration was below 3%. NCT04716569 [ 50 ] Mild Egypt 57 IVR significantly reduced durations of fever, cough, dyspnea, and anosmia, as well as the duration of detectable virus in the upper respiratory tract. Low (small sample size) Larger studies in patients with COVID-19 are needed to further investigate the therapeutic potential of IVR (eg, NCT04529525).…”
Section: Physiopathology Of Covid-19 Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… Low (small sample size) In all the study population, the incidence of clinical deterioration was below 3%. NCT04716569 [ 50 ] Mild Egypt 57 IVR significantly reduced durations of fever, cough, dyspnea, and anosmia, as well as the duration of detectable virus in the upper respiratory tract. Low (small sample size) Larger studies in patients with COVID-19 are needed to further investigate the therapeutic potential of IVR (eg, NCT04529525).…”
Section: Physiopathology Of Covid-19 Diseasementioning
confidence: 99%
“…Other repurposed drugs potentially targeting multiple steps of the SARS-CoV-2 life cycle are currently being tested, such as ivermectin (IVM), a broad-spectrum antiparasitic agent with previously reported antiviral activity in vitro [ 47 , 48 , 49 ]. Although a small study on 57 patients with mild COVID-19 showed a reduction in symptom duration and viral detection in the URT of treated patients [ 50 ], no robust evidence to support its clinical use was provided by other studies [ 51 , 52 ] or by a recent Cochrane meta-analysis [ 53 ].…”
Section: New Therapeutic Optionsmentioning
confidence: 99%
“…In a paper published by Aref et al [129] the nasal delivery of Ivermectin was discussed. Mucoadhesive nanosuspension was developed as a drug delivery platform to investigate possible effects in mild COVID-19 patients.…”
Section: Nasal Administration Of Ivermectinmentioning
confidence: 99%
“…Multiple RCTs have studied ivermectin use in COVID-19 patients. Some RCTs could not found any clinical efficacy of ivermectin [63][64][65], while others have reported faster time to recovery of COVID-19 disease [66][67][68][69][70], a remarkable decrease of cytokines and inflammatory markers [67,68], faster viral clearance [71], or decrease in mortality rate [67,68] in participants who received ivermectin in comparison with the standard treatment protocol. Nevertheless, the majority of these RCTs had methodological issues like small sample sizes, various ivermectin dosages, and different concomitant drugs given to the patients.…”
Section: Synthetic Drugsmentioning
confidence: 99%